2016
DOI: 10.9758/cpn.2016.14.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine versus Sertraline: An Observational, Open-labeled and 12 Weeks Follow-up Study on Efficacy and Tolerability

Abstract: ObjectiveIn this open-labeled, 12 weeks follow-up study, we aimed to compare the efficacy and tolerability of agomelatine with sertralineMethodsThe outpatients of adult psychiatry clinic who have a new onset of depression and diagnosed as ‘major depressive episode’ by clinician according to the Diagnostic and Statistical Manual of Mental Disorders 4th edition and prescribed agomelatine (25 mg/day) or sertraline (50 mg/day) were included in the study.ResultsThe decline of mean Montgomery-Asberg Depression Ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study is a part of a comprehensive project to assess the efficacy and tolerability profiles of agomelatine and sertraline, the first article of which was published in 2016 [5] and included an efficacy and general tolerability profile. More specific issues related to drugs and their effect on sleep, sexuality, and metabolic parameters are covered in the present study.…”
Section: Study Design and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a part of a comprehensive project to assess the efficacy and tolerability profiles of agomelatine and sertraline, the first article of which was published in 2016 [5] and included an efficacy and general tolerability profile. More specific issues related to drugs and their effect on sleep, sexuality, and metabolic parameters are covered in the present study.…”
Section: Study Design and Materialsmentioning
confidence: 99%
“…Comparative studies of agomelatine with selective serotonin re-uptake inhibitors (SSRIs) or serotoninnoradrenaline re-uptake inhibitors (SNRIs) have demonstrated that agomelatine has a favourable tolerability profile [4][5][6]. Discontinuations due to adverse effects have been found to be fewer in patients using agomelatine when compared to SSRI or SNRIs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, circadian rhythm and melatonin may be associated with depression [73,74]. Agomelatine, a MT1 and MT2 receptor agonist, is the first melatonin receptor ligand to demonstrate antidepressant effects in animal model experiments [75,76]. In a study with Flinders Sensitive Line rats, Overstreet et al showed that agomelatine reduced immobility time in the forced swim test (FST) [77].…”
Section: Antidepressant-like Actions Of Melatoninmentioning
confidence: 99%
“… 28 In an open-label, observational follow-up study, agomelatine’s efficacy was not significantly different from sertraline. 29 A pooled analysis of 4 follow-up clinical trials revealed that agomelatine is at least as efficacious as escitalopram, fluoxetine, and sertraline. 30 In addition, a meta-analysis revealed that agomelatine had similar efficacy with standard antidepressants.…”
Section: Discussionmentioning
confidence: 99%